Efficacy of Oral Nutritional Supplements in Patients Undergoing Surgical Intervention for Hip Fracture. (7th May 2022) - Ashkenazi, Itay; Rotman, Dani; Amzalleg, Nissan; Graif, Nadav; Amal Khoury,; Ben-Tov, Tomer; Steinberg, Ely
Introduction: Malnutrition is considered a risk factor among geriatric individuals with hip fracture, affecting functional healing and recovery, increasing healthcare spending, and associated with high mortality. In this study, we sought to evaluate the clinical efficacy of oral nutritional supplements in geriatric patients undergoing surgery for hip fracture.Material and Methods: We retrospectively analyzed data of 1625 consecutive patients who underwent fixation or arthroplasty for hip fracture in a tertiary medical center between 2017 and 2020. Patients who had no available albumin or body mass index levels were excluded. The study group is of patients who received an advanced formula in the form of an oral nutritional supplement (ONS), and the control group of patients that received no ONS. Peri- and postoperative complications, readmissions, short-term mortality, and albumin levels were compared between the 2 groups.Results: The final cohort included 1123 patients, 298 in the study group and 825 controls, with a follow-up of at least 1-year. Provision of the advanced enriched formula was not associated with 30-day, 90-day, or 1-year mortality (P = .62, P = .52, and P = .72, respectively) or any perioperative complications, such as 30-day or 90-day readmission (P = .37 and P = .1, respectively), revision surgery of any cause (P = .35), and postoperative infection rates (P = .73). Albumin levels on admission and the minimum albumin levels during hospitalization were similar between the groups, but they were significantly higher in the study group before discharge (33.42 g/L vs. 32.79 g/L, P = .01).Discussion: The use of an ONS was not associated with reduced perioperative complications or mortality, although it did affect nutritional status, as indicated by increased albumin levels, a known marker of nutritional status.Conclusions. While current findings do not support ONS use to minimize major postoperative complication after hip fracture surgery, further long-term study is warranted to evaluate subjective and functional outcomes associated with improved nutritional status.